Systematic Literature Review: Optimizing Classroom Management in the Implementation of Differentiated Learning to Diverse Student Learning Styles - Yona Anggelina Wulandari (Journal of Innovation in Teaching and Instructional Media, 2026)
This study aims to synthesize evidence on optimizing classroom management practices in implementing differentiated learning to accommodate diverse student learning styles (visual, auditory, and kinesthetic) in elementary education. Employing the Systematic Literature Review (SLR) method article searches were conducted across Scopus, and Google Scholar databases for publications between 2021-2026, with 15 peer-reviewed articles meeting inclusion criteria and analyzed using thematic synthesis. Findings reveal that optimizing classroom management requires four key dimensions: flexible classroom arrangements supporting varied activities, proactive behavior management promoting student autonomy, efficient time management for simultaneous multiple activities, and ongoing formative assessment to adjust instruction—strategies that teachers report increase student engagement across diverse learning styles. The novelty of this review lies in its integrated optimization framework connecting classroom management theory with differentiated instruction principles specifically for accommodating learning style diversity, addressing a critical gap in existing literature. Practical implications guide teachers and school leaders in redesigning classroom management approaches, while informing teacher training programs and school mentoring initiatives focused on creating inclusive learning environments. This research advances educational management by providing an evidence-based framework for optimizing classroom management in differentiated settings, offering both theoretical contributions and actionable insights for practitioners accommodating diverse learners.